Řízení pojistitelných rizik ve stavebním podniku - Jégl, Adam (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Tato bakalářská práce je věnována pojistitelným rizikům ve stavebním podniku. V teoretické části se budeme věnovat identifikaci rizik, jejich zatřídění a následné redukci, či úplné eliminaci. Praktická část se věnuje situaci, kdy pro konkrétní firmu poptáváme nabídky pojištění skrze celé spektrum trhu. Tyto nabídky následně vyhodnocujeme.

This thesis is devoted to the insurable risks in the construction company. The theoretical part will be devoted to identifying risks, their classification and subsequent reduction or complete elimination. The practical part deals with the situation where we are looking for a particular company offers insurance through the whole spectrum of the market. These offers then evaluate.
Management of insurable risks in construction company
Keywords: Rizika; pojištění; pojišťovny; výluky; návrh; odpovědnost; stavební a montážní pojištění; Risks; insurance; insurance companies; lockouts; draft; liability; construction all risk/erection all risk insurance